EXPLORING THE COMMUNICATIVE-NESS OF INDONESIAN ENGLISH COURSEBOOK: A CONTENT ANALYSIS - Sibakhul Milad Malik Hidayatulloh; Riffat Haqhani Zulkifli (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2022)
One thing cannot be denied from teaching and learning process is teaching material and methodology. They are often used interchangeably. Therefore, the creation of the teaching materials is underpinned based on the methodology that has been widely used and existed. Communicative Language Teaching (CLT) as the methodology has been widely implemented in the classroom and materials in teaching and learning language. However, the CLT principles in the textbook are not much evaluated. Therefore, this research aims to evaluate the CLT principles in the English textbook in Indonesia, to be exact Bahasa Inggris SMA Kelas 11 Semester 2 Textbook for Secondary Students in Indonesia. In evaluation process, the researchers used an adopted textbook’s evaluation checklist from Grant’s and Cunningsworth’s evaluation tools. Furthermore, there are five aspects to be focused which are the material, CLT claims, activities, provided skills, and tasks in the textbook. The findings showed that the textbook is not really implementing the principles of CLT. Moreover, it can be recognized from its activity and skills. Therefore, several aspects such as task, activity, and skills are needed to be improved. At the end of the chapter, suggestion for improving is also attached to improve the coursebook.